Synthetic Curcumin Analogs in the Treatment of Cancer: A Literature Review - Mardaneh, Pegah; Lavian, Salime; Bagherniya, Mohammad; Roufogalis, Basil D.; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2025)
Treatment of cancer, one of the most fatal diseases in the present century, has become a topic of global concern. Unfavorable unintentional effects of chemotherapy and radiation treatments have been the main reasons for the research on the discovery of drugs with a broader spectrum of effectiveness and efficiency, with minimal side effects. Curcumin (diferuloylmethane) is a naturally occurring phenolic structure with anticancer properties through its inhibition of cell multiplication, metastasis, and prolongation of cell cycle suppression of apoptosis in various tumor cells. The primary restriction regarding the use of curcumin in cancer treatment is related to poor bioavailability and unfavorable pharmacokinetic profiles of curcumin due to its poor absorption rate, fast metabolism, and systemic elimination. A variety of ways have been proposed to overcome these limitations. With this background, the present study focuses on providing a comprehensive overview of the anticancer properties of curcumin derivatives and the synthesis of curcumin analogs with application to different types of cancers. The regulation of various target and signaling pathways is considered in various cancers, including breast, gastrointestinal, pancreatic, prostate, skin, and lung cancers. A review of the literature indicates that modifying the structure of curcumin through the substitution of the phenyl group and unsaturated carbon branch around the two main sites of oxygen can result in the improvement of physical and chemical properties, as well as the enhancement of physiological activities of the curcumin molecule and the anti-cancer activities of this polyphenol. Curcumin analogs demonstrate anticancer properties at multiple targets at different cell stages and by various signaling biochemical pathways. These include cytokines, transcription factors, growth factors, and modulation of genes involved in cellular proliferation and apoptosis in breast, gastrointestinal, skin, prostate, and lung cancers, thereby mitigating tumor progression.
Keywords: Curcumin